PENGARUH RASIO KEMANDIRIAN, RASIO EFEKTIVITAS, DAN RASIO EFISIENSI TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN GORONTALO - Buka, Nurul Farha M.; Hiola, Yustina (JSAP : Journal Syariah and Accounting Public, 2021)
The research was conducted at department of regional financial and assets of Gorontalo Regency. The objective was to determine the influence of dependent variable there are independency, effectiveness, and efficiency ratio to the dependent variable, namely Original local government revenue (PAD). The method used multiple linear regressions. The results was the independence ratio, effectiveness ratio, and efficiency ratio together have a positive and significant effect, while partially the independence and effectiveness ratio have an effect on Original local government revenue where if the independence ratio and effectiveness ratio have increased, the original regional income will increase. Also, while the efficiency ratio has a negative and significant effect because when the efficiency ratio increases, local revenue will decrease.